Estimation of the frequency of hexosaminidase a variant alleles in the American Jewish population. - Greenberg, D A (1982)
There appear to be several alleles of the hexosaminidase A (HEX A) gene that lead to different clinical syndromes. In addition to the infantile-onset Tay-Sachs disease (TSD), there is a juvenile-onset and an adult-onset form, which are also characterized by low HEX A levels. There are also apparently healthy adults with low HEX A activity. Based primarily on data from population screening for TSD carrier status, we estimate the allele frequency of the combined variant alleles for which data are available to be about 4.5 x 10(-4) and the frequency of adults showing zero HEX A levels (when tested using artificial substrate) to be about 1:67,000. The implications for population screening and prenatal diagnosis are discussed.